Learning the language of scripture: origen, wisdom, and the logic of interpretation - James, Mark Randall (Studies in Systematic Theology, 2021)
Acknowledgements -- Abbreviations -- Introduction -- 1 The Problem of Hermeneutic Arbitrariness -- 2 Origen and Arbitrariness -- 3 Method: Descriptive Logic -- 4 Learning the Language of Scripture -- 1 Origen and Stoic Logic -- 1 Stoic Philosophy of Language -- 2 Origen on Language and Logic -- 3 Conclusion -- 2 From Lexis to Logos -- 1 The Pedagogy of the Logos -- 2 Elements of the Movement from Lexis to Logos -- 3 Conclusion -- 3 The Pragmatics of Scriptural Utterances -- 1 Deixis -- 2 Implicature -- 3 Conclusion -- 4 The Grammar of Scriptural Language -- 1 Inquiry and Vagueness -- 2 Habits of Scripture -- 3 Invention -- 4 Conclusion -- 5 The Deification of Discourse -- 1 Bold Speech -- 2 Parrhesia and Deification -- 3 Conclusion -- 6 Origenism as Pragmatism: A Sketch of a Sapiential Hermeneutic -- 1 Wisdom -- 2 Scripture and Philosophy -- 3 Sapiential Interpretation -- 4 Towards a Sapiential Theology of Scripture -- Works Cited -- Index of Citations -- Index of Names and Subjects.